UZBEK CINEMA: SLOW REVIVAL - MESAMED, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2004)
The Soviet Union’s collapse not only had an impact on the sociopolitical situation in the former Soviet republics, but also on the state of affairs in science and art, including cinematography. Marked by many common or similar traits, Soviet cinema, as the unity and synthesis of its national components, disintegrated into purely national parts, finally breaking free from Moscow’s ideological grasp. This also led to the cinema art (and its parts) of the newly independent states breaking its decades-long ties with the cinematography of other former union republics, primarily Russia. The difficulties experienced by all these countries during the transition to a market economy also took their toll on the national film industry, including in Uzbekistan, the only post-Soviet republic in which local cinematography has centralized financial support. (When a film production and rental market is just forming, it is difficult to overestimate the state’s participation in encouraging and supporting this intricate process.)